Berberine attenuates septic cardiomyopathy by inhibiting TLR4/NF-κB signalling in rats. (1st January 2021) - Chen, Huiqi; Liu, Qian; Liu, Xiangqi; Jin, Jinlan
Abstract: Context: Berberine (Ber) can increase the survival rate of septic mice and inhibit inflammation, but whether it has a protective effect on septic cardiomyopathy (SCM) is unclear. Objective: To investigate whether Ber ameliorates SCM in a rat model and its potential mechanism. Materials and methods: Male SD rats were randomly divided into three groups: control (Con, n = 6) (DD H2 O, 2 mL/100 g, ig, qd × 3 d, then saline, 10 mg/kg, ip); sepsis [LPS (lipopolysaccharide), n = 18] (LPS 10 mg/kg instead of saline, ip); and berberine intervention (Ber, n = 18) (Ber, 50 mg/kg instead of DD H2 O, ig, qd × 3 d, LPS instead of saline, ip). Hemodynamics, HE staining, ELISA and western blot were performed at 6, 24, and 48 h after intraperitoneal injection of LPS to evaluate the effect of berberine in septic rats. Result: Berberine could recover myocardial injury by partially increased ± dp/dt max (1151, 445 mmHg/s) and LVEDP levels (1.49 mmHg) with LPS-induced rats, as well as an ameliorated increase of cTnT (217.53 pg/mL) in the Ber group compared with that in the LPS group (at 24 h). In addition, HE staining results showed that berberine attenuated the myocardial cell swelling induced by LPS. In contrast to the LPS group, the up-regulation of TLR4, p65 TNF-α, and IL-1β were attenuated in the Ber group. Discussion and conclusions: Berberine showed a protective effect on septic cardiomyopathy rats possibly through inhibiting the activation of TLR4/NF-κB signalling pathway. Whether it improves SCM through other mechanisms is our ongoing research.